[OP.5A.04] EVALUATION OF RETINAL MICROPERFUSION AND ARTERIOLAR STRUCTURE IN PATIENTS WITH FIBROMUSCULAR DYSPLASIA. THE PRELIMINARY DATA OF THE POLISH REGISTRY FOR FIBROMUSCULAR DYSPLASIA. (September 2016) - Warchol-Celinska, E.; Gosk-Przybylek, M.; Harazny, J.; Binczyk, E.; Szymanek, K.; Hanus, K.; Jozwik-Plebanek, K.; Florczak, E.; Prejbisz, A.; Cendrowska-Demkow, I.; Dobrowolski, P.; Klisiewicz, A.; et al.
Abstract : Objective: To compare retinal microperfusion and arteriolal structure between patients with fibromuscular dysplasia (FMD) enrolled to the ARCADIA-POL registry and patients with essential hypertension (EHT). Design and method: From the first 84 patients with confirmed FMD in any vascular bed enrolled in the ARCADIA-POL registry in 2015 (instituted on the basis of as Polish-French collaboration), we analyzed data regarding retinal microperfusion and arteriolar structure available from 70 patients (51F, 19 M, mean age: 41.9 ± 14.8 years). All patients underwent detailed clinical evaluation including ABPM, biochemical evaluation and biobanking as well as duplex Doppler of carotid and abdominal arteries and whole body angio-CT. We also evaluated 42 age, gender, body mass index, glycemic status, blood pressure levels and number of medication (p > 0.05) matched patients (24 F, 18 M, mean age: 46.1 ± 10.5 years) with EHT. Retinal microperfusion (RCF) and retinal arterioles were assessed using scanning laser Doppler flowmetry (SLDF). The parameters of retinal morphology: outer diameter (AD), lumen diameter (LD), wall/lumen ratio (WLR), wall thickness (WT), and wall cross-sectional area (WCSA) were determined by automatic full-field perfusion imaging analysis (AFFPIA V.4.011). Results: When comparing 70 patients with FMD to the matched group of patients with EHT we observed no significant differences in parameters describing retinal morphology. In further analysis we included 23 patients with confirmed FMD in carotid and/or intracranial arteries (22F, 1 M, mean age 43.6 ± 15.2ys) and we compared them to 26 matched patients (p < 0.05) with EHT (23F, 3 M, mean age: 48.8 ± 10.1 years). Patients with FMD affecting carotid and/or intracranial arteries were characterized by lower WLR (0.34 ± 0.08 vs. 0.39 ± 0.08, p = 0.048) and tendency towards lower WT (12.9 ± 3.7 vs.14.5 ± 3.3 μm, p = 0.15) and lower WCSA (3691.6 ± 1359.6 vs. 4106.8 ± 1222.1 μm2, p = 0.29) as compared to patients with EHT. There was no differences in AD, LD, nor RCF between the groups. Conclusions: In our ongoing ARCADIA-POL study we observed significant changes in retinal arterioles structure in patients with confirmed FMD in carotid and/or intracranial arteries.